1988
DOI: 10.1128/cmr.1.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the epidemiology and pathogenesis of clinically significant Vibrio spp

Abstract: Recent taxonomic advances have now implicated several different Vibrio species as human pathogens. While the most common clinical presentation of Vibrio infection continues to be gastroenteritis, an increasing number of extraintestinal infections are being reported, particularly in immunocompromised individuals. Detection of Vibrio infections requires a good clinical history and the use of appropriate isolation and identification procedures by the laboratory to confirm illnesses attributed to Vibrio species. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
175
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(179 citation statements)
references
References 201 publications
(80 reference statements)
4
175
0
Order By: Relevance
“…DISCUSSION In 1979 the name V. vulnificus was given to a Vibrio species of which the characteristics were described in 1976 [9,10]. V. vulnificus has been isolated from numerous marine environments; the highest densities are generally found in areas of high temperature and low to moderate salinity [1]. An in-vitro study of growth characteristics of environmental isolates of V. vulnificus demonstrated salinity optima of 10-20% NaCl and a temperature optimum of 37 'C [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION In 1979 the name V. vulnificus was given to a Vibrio species of which the characteristics were described in 1976 [9,10]. V. vulnificus has been isolated from numerous marine environments; the highest densities are generally found in areas of high temperature and low to moderate salinity [1]. An in-vitro study of growth characteristics of environmental isolates of V. vulnificus demonstrated salinity optima of 10-20% NaCl and a temperature optimum of 37 'C [11].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four Vibrio species are currently recognized in the genus, a third of which are known to be pathogenic for humans [1]. The halophilic Vibrio species, V. parahaemolyticuas, V. alginolyticus and V. vulnificus are known to be involved in intestinal as well as in extra-intestinal human infections [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with pre-existing liver or blood disorders, or a history of alcohol abuse, are more susceptible to infection with V. vulnificus, which results in elevated serum iron levels; the resistance of V. vulnificus to killing by human serum is mediated by the presence of excess iron [2].…”
Section: Resultsmentioning
confidence: 99%
“…The evaluations carried out by West [1] indicated that strains of V. vulnificus are more resistant to lysis by complement than are V. parahaemolyticus and V. cholerae, and that during invasion it can activate both the classic and alternate pathways [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation